Detection of the impact of a tropical cyclonic system on the dynamics and energetics of the atmosphere using wind profiler radar. (1st September 2022) - Sivan, C.; Rakesh, V.; Manoj, M.G.; Satheesan, K.; Abhilash, S.; Mohanakumar, K.
Abstract: Rapid changes in the tropospheric circulation features associated with the overhead passage of the Gaja cyclonic system over the 205 MHz Stratosphere Troposphere wind profiler radar observations at Kochi (10.03° N, 76.33° E), India, have been studied. The severe cyclonic system formed in the southeast Indian Peninsular region weakened into a depression after landfall near the Tamil Nadu coast. On 16th November 2018, the cyclonic system crossed the Western Ghats and travelled westward at 33 knots over the ST radar site at Kochi in the evening. Later it reached the Arabian Sea and intensified again into a severe cyclone. Continuous observations of the vertical structure of the wind pattern at 4-min intervals from the wind profiler radar have been examined. The impact of the transit of the cyclonic system extends up to a height of 13 km in the atmosphere. The vertical distribution of turbulent kinetic energy in the atmosphere indicates a sudden disruption in the tropospheric levels at the time of storm passage. The cyclonic system traversed over the Western Ghats positioned at an altitude of 2500 m. It crossed the radar site at the mean sea level after passing a horizontal distance of 100 km. The abrupt changes in the topographical conditions generate atmospheric gravity waves in the leeward side of the Western Ghats, as observed from the ST radar, are presented. During the period, changes in surface parameters were evaluated using co-located automatic weather station (AWS) data. Satellite information and Doppler weather radar observations from Kochi have also supplemented the investigation. Highlights: Changes in the dynamics and energetics of the atmosphere associated with the storm passage were reported. The zonal and vertical winds show sudden changes at the time of transit of the cyclonic system. The turbulent kinetic energy and momentum flux showed abrupt enhancement up to 13 km. Atmospheric gravity waves generated during the storm passage propagate upward. The impact of the transit of the cyclonic system is minimal in the upper troposphere.